The Impact of Seasonal Changes on the Land Cover of Lake Hamrin: A Comparative Study of Dry and Wet Seasons - Abdul-Razak, Shamam B.; Abduljabbar , Hameed M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
This study conducted a thorough analysis of changes in land cover components of the Lake Hamrin area, located within Diyala Governorate, Iraq, focusing on the influence of human and climatic factors. Human variables included the rate of water release from the Darbandikhan Dam, while climatic factors encompassed fluctuations in temperature and annual rainfall. These factors significantly impact the lake, the largest body of water in the region, and other land cover components, leading to disruptions in the overall ecological balance.Two satellite images from 2024 were analyzed for this research, representing two distinct seasonal periods: the first image was captured in April, following the conclusion of the rainy season, while the second was taken in October, after the summer months. Data obtained from the Landsat 9 OLI satellite, provided by the United States Geological Survey (USGS), were employed, targeting the specific area within track number 168-36. The dataset was processed using ENVI version 5.3, an advanced tool dedicated to spatial data analysis. The analysis of land cover changes in the Hamrin Lake area was conducted using the Maximum Likelihood Algorithm (MLA), focusing specifically on the interactions between climatic and human factors affecting water mass. This method allowed for a comprehensive evaluation of changes in water mass area and their subsequent impact on other land cover components, with the overall classification accuracy serving as a key performance metric. The findings revealed a significant correlation between the lake's water mass area and adjacent land classes, which revealed notable variations in the area of water bodies between the spring and autumn seasons, which affected various land cover categories and, consequently, the regional ecosystem